2011
DOI: 10.1002/jmv.22040
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus‐specific IgA in saliva and viral antigen in the parotid gland in patients with hemorrhagic fever with renal syndrome

Abstract: The Hantavirus genus comprises rodent borne, zoonotic viruses of the Bunyaviridae family that cause hemorrhagic fever with renal syndrome (HFRS) in Eurasia and hantavirus cardiopulmonary syndrome (HCPS) in the Americas. Rodent saliva contains infectious hantavirus and evidence suggests that hantavirus is also shed in human saliva, but person-to-person transmission is rare. In saliva, immunoglobulin (Ig) A is the predominant immunoglobulin class. Secretory IgA serves as an important first line of defence on epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In our study, one limitation was that neutralizing antibodies were not analysed. We detected an inverse association between hantavirus-specific IgG and IgA antibody titres and viral load, as previously indicated for IgG 13 , 24 and salivary IgA 25 . However, in contrast to IgG titres, we did not observe any association with disease severity for IgA and IgM titres.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, one limitation was that neutralizing antibodies were not analysed. We detected an inverse association between hantavirus-specific IgG and IgA antibody titres and viral load, as previously indicated for IgG 13 , 24 and salivary IgA 25 . However, in contrast to IgG titres, we did not observe any association with disease severity for IgA and IgM titres.…”
Section: Discussionsupporting
confidence: 87%
“…Petterson et al could demonstrate that hantavirus RNA was found in saliva few days after disease onset [ 41 ]. The association between the anti-Hantavirus IgA and Hantavirus RNA in saliva was inverse, the same is true for detecting RNA and antigen in endothelial cells within the parotid gland of HFRS patients [ 42 ]. In a recent study, the anti-Hantavirus antibodies in saliva was detected in a risk group in farms in Yorkshire, UK [ 43 ].…”
Section: Main Textmentioning
confidence: 99%
“…16 In suppurative parotitis, bacteria such as Staphylococcus aureus and oral aerobes/anaerobes are the agents involved and are more frequently encountered in debilitated, dehydrated and elderly patients who have undergone surgery, while in non-suppurative parotitis the most frequent cause is mumps, although influenza, parainfluenza, coxsackie, echo viruses, CMV, HSV, HIV, EBV, lymphocytic choriomeningitis virus, hemorrhagic fever viruses such as hantavirus, dengue virus, Mycobacterium tuberculosis and other atypical microbacteria may also, rarely, cause parotitis. 12,13,16 Clinical findings are very similar among the hemorrhagic fever viruses which caused by parotitis. So serologic and molecular tests are essential for the differential diagnosis of them.…”
Section: Discussionmentioning
confidence: 76%
“…12 Pettersson et al were detected hantavirus-specific IgA in saliva and viral antigen in the parotid gland in patients with hemorrhagic fever with renal syndrome. 13 …”
Section: Other Similar and Contrasting Cases In The Literaturementioning
confidence: 97%
See 1 more Smart Citation